2017
DOI: 10.1121/1.4984623
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional-printed membrane-type acoustic metamaterial for low frequency sound attenuation

Abstract: Membrane-type acoustic metamaterials have received much attention for low-frequency sound manipulation, especially in the form of decorated membrane resonators. In this paper, such resonators are obtained using fused deposition modeling. Beyond the practical aspects provided by this manufacturing method, the low density of the flexible filament used increases their effectiveness. Indeed, the mass usually added to the membrane center can easily be divided into several disjoint elements. Using rotary inertia of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…provide a solution to this problem, rely on additive manufacturing technologies due to their topological and geometrical complexity and characteristics [6,13,16]. This kind of technology, while presenting itself as a potential promising manufacturing option in the future, still faces many challenges nowadays, especially in terms of processing times and dimensional tolerances (see Section 4.2 for a further insight on that), which are of utmost importance in order to produce effective acoustic metamaterials in a practical manner.…”
Section: Region Of Interestmentioning
confidence: 99%
“…provide a solution to this problem, rely on additive manufacturing technologies due to their topological and geometrical complexity and characteristics [6,13,16]. This kind of technology, while presenting itself as a potential promising manufacturing option in the future, still faces many challenges nowadays, especially in terms of processing times and dimensional tolerances (see Section 4.2 for a further insight on that), which are of utmost importance in order to produce effective acoustic metamaterials in a practical manner.…”
Section: Region Of Interestmentioning
confidence: 99%
“…In contrast to previous investigations, wherein the mass weights were concentrated at the centers of the membranes, other research efforts accomplished the fabrication of specimens with coaxial rings attached to the membranes. [78] A novel membrane-type AM, which comprised rectangular membranes to which several semicircular mass blocks were adhered, was proposed by Mei et al [72] Almost total absorption was achieved from the energy conversion and multiple resonance. In addition, the absorption frequencies at which multiple resonances occurred could be manipulated through changes in the weights of the semicircular mass blocks or in the distances between these mass blocks.…”
Section: Membrane-type Structurementioning
confidence: 99%
“…Thus, the reflected phase of the sound wave will be shifted compared with the incident phase. Previous works have demonstrated that physical parameters of the material (i.e., the mass density, Young's modulus, and Poisson's ratio), the geometric dimensions of the unit, and the working frequency all have influences on the sound behavior of the unit, including reflected ratio and phase [30][31][32]. In the present study, in order to guarantee the unitary subwavelength thickness of entire metasurface and for the simplicity of design, the thicknesses of the unit and the membrane are fixed.…”
Section: Design Of the Modelmentioning
confidence: 99%